Expression profile of GBP4 and IL20RB genes in the development and progression of CRC - Maedeh Khosravi (Cellular, Molecular and Biomedical Reports)
Colorectal cancer (CRC) is a significant global health concern with a rising incidence among younger populations. This study aims to better understand the molecular mechanisms underlying CRC by evaluating the expression of two key genes, GBP4 and IL20RB, at various stages of CRC development and progression. GBP4, a member of the guanylate-binding protein (GBP) family, plays a crucial role in inflammation and immunity, while IL20RB, an interleukin-20 receptor subunit, is implicated in chronic inflammation and malignancies. The selection of these particular genes was based on their potential roles as biomarkers in CRC research. Tumor tissue samples (n=40) from patients with colorectal cancer and adjacent normal tissues were obtained from the Iranian Tumor Bank. Following total RNA extraction and cDNA synthesis, the expression levels of GBP4 and IL20RB were measured using the qRT-PCR technique. Finally, the diagnostic capacities of both gene expressions were evaluated through ROC curve analysis. GBP4 was significantly downregulated in colorectal tumors (p-value = 0.03), as well as in both non-metastatic (p-value = 0.04) and metastatic samples (p-value = 0.002) compared to adjacent normal tissues. Additionally, IL20RB was significantly upregulated in non-metastatic tumor tissues (p-value = 0.03) compared to adjacent normal tissues, but its expression showed no significant difference in metastatic tumor tissues compared to normal tissues. The expression level of GBP4 decreases during the development and progression of CRC, while IL20RB is primarily associated with CRC development, specifically in non-metastatic stages. Both genes may serve as promising prognostic biomarkers for CRC.